Tumour‐cell‐derived complement components C1r and C1s promote growth of cutaneous squamous cell carcinoma. (1st March 2020) - Riihilä, P.; Viiklepp, K.; Nissinen, L.; Farshchian, M.; Kallajoki, M.; Kivisaari, A.; Meri, S.; Peltonen, J.; Peltonen, S.; Kähäri, V.‐M.
Summary: Background: The incidence of epidermal keratinocyte‐derived cutaneous squamous cell carcinoma (cSCC) is increasing worldwide. Objectives: To study the role of the complement classical pathway components C1q, C1r and C1s in the progression of cSCC. Methods: The mRNA levels of C1Q subunits and C1R and C1S in cSCC cell lines, normal human epidermal keratinocytes, cSCC tumours in vivo and normal skin were analysed with quantitative real‐time polymerase chain reaction. The production of C1r and C1s was determined with Western blotting. The expression of C1r and C1s in tissue samples in vivo was analysed with immunohistochemistry and further investigated in human cSCC xenografts by knocking down C1r and C1s. Results: Significantly elevated C1R and C1S mRNA levels and production of C1r and C1s were detected in cSCC cells, compared with normal human epidermal keratinocytes. The mRNA levels of C1R and C1S were markedly elevated in cSCC tumours in vivo compared with normal skin. Abundant expression of C1r and C1s by tumour cells was detected in invasive sporadic cSCCs and recessive dystrophic epidermolysis bullosa‐associated cSCCs, whereas the expression of C1r and C1s was lower in cSCC in situ, actinic keratosis and normal skin. Knockdown of C1r and C1s expression in cSCC cells inhibited activation of extracellular signal‐related kinase 1/2 and Akt, promoted apoptosis of cSCC cells and significantly suppressed growth and vascularization of human cSCC xenograft tumours in vivo . Conclusions: These results provide evidence for the role of tumour‐cell‐derived C1r and C1s in the progression of cSCC and identify them as biomarkers and putative therapeutic targets in cSCC. What's already known about this topic? The incidences of actinic keratosis, cutaneous squamous cell carcinoma (cSCC) in situ and invasive cSCC are increasing globally. Few specific biomarkers for progression of cSCC have been identified, and no biological markers are in clinical use to predict the aggressiveness of actinic keratosis, cSCC in situ and invasive cSCC. What does this study add? Our results provide novel evidence for the role of complement classical pathway components C1r and C1s in the progression of cSCC. What is the translational message? Our results identify complement classical pathway components C1r and C1s as biomarkers and putative therapeutic targets in cSCC.